Young People's Perceptions of the 12-Steps' Role in Supporting Their Recovery (or Not). Issue 5 (8th August 2019) - Nash, Angela J.; Hennessy, Emily A.; Collier, Crystal; Kelly, John F.
Abstract: Although 12-step participation is related to improved outcomes, young people's 12-step involvement is rare. There is limited research on the role of 12-step philosophy and practices for supporting young people's recovery or addressing why so few engage in 12-step practices. To explore these issues, content analysis was applied to qualitative data from two prior studies conducted with individuals who participated in an Alternative Peer Group (APG), a 12-step facilitated adolescent recovery support model. Findings revealed new information on barriers to 12-step involvement and suggest strategies for addressing barriers, boosting motivation, and changing young people's perceptions of 12-step philosophy and practices.